2005
DOI: 10.4102/curationis.v28i4.1009
|View full text |Cite
|
Sign up to set email alerts
|

Accompaniment needs of nursing students related to the dying patient

Abstract: Nurse educators are responsible for accompanying students towards becoming capable, competent professional nurses who are a credit to themselves, their patients, colleagues and profession. Student nurses need, therefore, to be taught to render comprehensive nursing care to patients in all stages of their lives, including when they are dying. Being confronted with human suffering and death is challenging and traumatic. Those exposed to such events on a daily basis need to have a solid foundation of self preserv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 11 publications
0
17
0
3
Order By: Relevance
“…Qualitative Assessment and Review Instrument (QARI), designed by the Joanna Briggs Institute, is used to facilitate critical appraisal, data extraction, and metaaggregation of the findings of qualitative studies. QARI includes the following 10 items: (1) there is a congruity between the stated philosophical perspective and the research methodology; (2) there is a congruity between the research methodology and the research question or objectives; (3) there is a congruity between the research methodology and the methods used to collect data; (4) there is a congruity between the research methodology and the representation of results; (5) there is a congruity between the research methodology and the interpretation of the results; (6) there is a statement locating the researcher culturally or theoretically; (7) the influence of the researcher on the research, and vice versa, is addressed; (8) participants, and their voices, are adequately represented; (9) the research is ethical according to current criteria or for recent studies, there is evidence of ethical approval by an appropriate body; and (10) conclusions are drawn in the research report do appear to flow from the analysis, or interpretation, of the data. The retrieved articles were assessed item by item and marked by yes, no, or unclear by two independent reviewers.…”
Section: Assessment Of Methodological Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…Qualitative Assessment and Review Instrument (QARI), designed by the Joanna Briggs Institute, is used to facilitate critical appraisal, data extraction, and metaaggregation of the findings of qualitative studies. QARI includes the following 10 items: (1) there is a congruity between the stated philosophical perspective and the research methodology; (2) there is a congruity between the research methodology and the research question or objectives; (3) there is a congruity between the research methodology and the methods used to collect data; (4) there is a congruity between the research methodology and the representation of results; (5) there is a congruity between the research methodology and the interpretation of the results; (6) there is a statement locating the researcher culturally or theoretically; (7) the influence of the researcher on the research, and vice versa, is addressed; (8) participants, and their voices, are adequately represented; (9) the research is ethical according to current criteria or for recent studies, there is evidence of ethical approval by an appropriate body; and (10) conclusions are drawn in the research report do appear to flow from the analysis, or interpretation, of the data. The retrieved articles were assessed item by item and marked by yes, no, or unclear by two independent reviewers.…”
Section: Assessment Of Methodological Qualitymentioning
confidence: 99%
“…13,22 Because of the heavy workload of nurses, many students felt abandoned because they did not receive enough guidance and support from the preceptors. 6,8,12,15 The interactions with the physicians were also very important parts of students' experiences. Some students reported that they were impressed by the physicians' professional behavior, claiming learned lots of knowledge from physicians.…”
Section: Students With the Surroundingsmentioning
confidence: 99%
“…4,7,8,13 Students Want to Learn More About Death Some students believe that they have received insufficient instruction and have indicated that they would like more workshops to learn about dying and death. Although the circumstances surrounding death are delicate, death is inevitable and one of the truly universal human experiences.…”
Section: Medical Students and Nurses Receive Limited Instruction Aboumentioning
confidence: 99%
“…They do not feel adequately trained and prepared to face such treatment situations in real life [9–11]. A learner’s perception of their ability to carry out a task, termed “perceived self-efficacy” (PSE) by Bandura, is a decisive element in a person’s commitment to complete the task in question.…”
Section: Introductionmentioning
confidence: 99%